Using the auxiliary hypothesis metatheorem prove ⊢ (∃x)A → (∃x) ( A ∧ (A ∨ B) )
Join Matchmaticians Affiliate Marketing
Program to earn up to a 50% commission on every question that your affiliated users ask or answer.
- closed
- 664 views
- $4.92
Related Questions
- Characterizing the Infinitely Visited Intersections in a Ride-Forever Path on a Directed Graph
- Questions about computability Theory, Logic
- Logic equation
- Logic Question 𝐴∨𝐵→𝐶⊢(𝐴→𝐶)∧(𝐵→𝐶)
- Combinatorics Questions: Card Pairs, Letter Arrangements, and Number Sequences
- 2 Player Limited Information Game
- Logic Question (𝐴→(𝐵→𝐶))→((𝐴→𝐵)→(𝐴→𝐶))
- Logic Question 𝐴∧(𝐵∨𝐶)⊢(𝐴∧𝐵)∨(𝐴∧𝐶)
The auxiliary hypothesis is: "Suppose that Γ ⊢ (∃x)A."
I don't understand the technique. Can you give a definition rather than an example?